PERKEMBANGAN KOMUNITAS JAWA DI KECAMATAN BIES KABUPATEN ACEH TENGAH (1931-2015) - Ihwanto -; Husaini -; Anwar Yoesoef (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2017)
ABSTRACTAppointed as the title is "The development of the Java community in the district of Central Aceh district Bies (1931-2015)", the purpose of this study were (1) to describe the Java community in the district of Central Aceh district Bies (1931 to 2015) in terms of demography and (2) to describe the development of the Java community in the district of Central Aceh district Bies (1931 to 2015) in terms of the interaction process. Writing this thesis uses a quantitative approach and methods of historical research, which consists of five working procedures, namely, the choice of theme, heuristics, Verification, Interpretation) and Historiography. Data collection is done by interview and documentation study. From the results of the study showed that: (1) the arrival of the Javanese community in District Bies began century 20th century precisely when programmed by the Dutch ethical politics. Java community continues to experience growth since 1931-2015. Based on the data found in 1998 the population of Java in the district Bies has reached 25 families or 100 people. That number continues to rise even in 2003 there were 50 families or 200 persons in the District Javanese Bies, in 2008 the number of households has reached 68 families or 272 people, in the year 2009 to 2012 the population of Javanese in District Bies back up to 94 families or 376 soul and even that amount to 2015 has reached 125 families or 500 people, and (2) the development of the Javanese in terms of interaction with the local population since 1931-2015 seen in many areas of life such as the field of marriage, livelihood, religion, language, gotong -royong, education, and infrastructure life (equipment, art and food).Keywords: Development, Community, Javanese  ABSTRAKSesuai dengan judul yang diangkat yaitu “Perkembangan Komunitas Jawa di Kecamatan Bies Kabupaten Aceh Tengah (1931-2015)”, maka tujuan penelitian ini adalah (1) untuk mendeskripsikan komunitas Jawa di kecamatan Bies kabupaten Aceh Tengah (1931-2015) ditinjau dari aspek demografi dan (2) untuk mendeskripsikan perkembangan komunitas Jawa di kecamatan Bies kabupaten Aceh Tengah (1931-2015) ditinjau dari proses interaksi. Penulisan skripsi ini menggunakan pendekatan kuantitatif dan metode penelitian sejarah, yang terdiri dari lima prosedur kerja yaitu, pemilihan tema, heuristik, Verifikasi, Interpretasi) dan Historiografi. Pengumpulan data dilakukan cara wawancara dan studi dokumentasi. Dari hasil penelitian dapat diketahui bahwa: (1) kedatangan komunitas Jawa di Kecamatan Bies dimulai abad abad ke-20 tepatnya saat diprogramkan politik etis oleh oleh Belanda. Komunitas Jawa terus mengalami perkembangan sejak 1931-2015. Berdasarkan data yang ditemukan tahun 1998 jumlah penduduk Jawa di Kecamatan Bies sudah mencapai 25 KK atau 100 jiwa. Jumlah itu terus naik bahkan di tahun 2003 terdapat 50 KK atau 200 jiwa etnis Jawa di Kecamatan Bies, di tahun 2008 jumlah KK sudah mencapai 68 KK atau 272 jiwa, ditahun 2009-2012 jumlah penduduk etnis Jawa di Kecamatan Bies kembali naik hingga 94 KK atau 376 jiwa dan bahkan jumlah itu sampai 2015 sudah mencapai 125 KK atau 500 jiwa, dan (2) perkembangan etnis Jawa di segi interaksi dengan penduduk setempat sejak 1931-2015 terlihat dalam berbagai bidang kehidupan seperti bidang perkawinan, mata pencaharian, agama, bahasa, gotong-royong, pendidikan, dan sarana prasarana kehidupan (peralatan, kesenian dan makanan).Kata Kunci: Perkembangan, Komunitas, Etnis Jawa